3 - The Quality of Nigeria’s Private Universities* - Erinosho, Olayiwola A.; Aina, Diji; Okhomina, Stephen; Temilola, Segun (Journal of Higher Education in Africa, 2008)
This study is about the quality of private universities in Nigeria. Three of them (Babcock, Bowen and Igbinedion), two mission-sponsored and one that is owned by an entrepreneur, were studied using six indicators of quality assurance that are outlined by GOS Ekhaguere for similar work in African universities. First, the data indicate that the institutions mount academic programmes in science, hu- manities and, most especially, in the social and management sciences. Second, there is gender parity among students and disparity among staff. Third, the mis- sion institutions are better positioned to give quality education. However, these private universities need to strengthen their staff and improve access to informa- tion and communication technologies. There is also room for improving the physical facilities. Overall, the study concludes that while it may be worthwhile to encour- age private investors in higher education, this should not be at the expense of public universities because the latter’s academic programmes are much more di- versified than those which are offered by the former.